Macroeconomic implications of oil-price shocks to emerging economies: A Markov regime-switching approach - Sophio Togonidze; Evžen Kočenda (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We investigate an impact of oil-price shocks on GDP and exchange rate dynamics in resource-heterogeneous economies. We employ a Markov regime-switching version of a vector autoregressive (VAR) model to allow for regime shifts, non-linear effects and timevarying parameters of the VAR process. Empirically we use quarterly data series in oil exporting, metal-exporting, and less-resource-intensive economies. On average, real GDP in oil-exporting economies exhibits substantial contraction, while for metal exporters there is a significant real GDP expansion suggesting an offsetting effect of metal exports on oil imports. We find that currency appreciation state is more persistent in oil- and metal exporting economies while less-resource-intensive economies remain longer in a currency depreciation state. Further evidence suggests existence of the counteracting forces such as foreign exchange interventions by authorities in oil-exporting economies. It also emerges that currency appreciation in oil-exporting economies is driven largely by economic performance rather than oil price movement.
Keywords: F44; E37; C11; E32; C22; C58; F31; Q43; 330; Emerging economies; Oil shocks; GDP; Markov regime-switching; Exchange rate; Oil exporters; Metal exporters